PTH-132 Outcomes following transplant for hepatitis c: a single centre study. (22nd June 2015) - Townsend, SA; Dhaliwal, H; Gunson, B; Mutimer, D
Abstract : Introduction: Liver disease from hepatitis C (HCV) is a leading indication for liver transplantation in the UK. HCV recurrence has a significant influence on graft and patient survival, but antiviral therapy has had poor tolerability and disappointing efficacy (low sustained virological response SVR rates) in the transplant setting. The use of antivirals has evolved over time, from interferon (IFN) monotherapy to combination IFN and ribavirin, and now includes the frequent use of direct acting antiviral drugs (DAAs), often as components of IFN-free regimens. We examined the outcome of 431 patients with hepatitis C who underwent liver transplantation at the Queen Elizabeth Hospital, Birmingham, and report the outcome of treatment and its possible effect on graft and patient survival. Method: Retrospective study of all patients transplanted for HCV at the Queen Elizabeth Liver Transplant Unit, Birmingham. Results: 431 patients with HCV were transplanted between 1988 and 2014. 174 patients had hepatocellular carcinoma (HCC) and 81 also had alcohol-related damage as a cofactor. 91 were female (21%) and 340 male (79%), with a mean age of 52 years at transplantation (range 27–69). Patient survival rates were 88%, 68% and 48%, at 1, 5 and 10 years respectively; graft survival was 86%, 65% and 46% for the same time intervals. The commonest causes of death were HCV recurrence n = 34 (20%), sepsis n = 33 (19%), recurrent HCC n = 30 (17%), and gastrointestinal bleeding n = 10 (5%). 28 patients required regrafting. The indications were recurrent disease n = 11 (39%), primary non-function n = 8 (29%), hepatic artery thrombosis n = 8 (29%), and chronic rejection n = 1 (3%). 109 patients received 118 courses of antiviral treatment post-transplant. 20 (17%) of these were IFN monotherapy, 61 (52%) IFN and ribavirin, 12 (10%) triple therapy with IFN, ribavirin and telapravir, and the remaining 25 (21%) were DDAs. The overall SVR rate was 57%. Those patients achieving SVR had significantly better survival than those who failed treatment, and also better than those never treated (5 year patient survival 95%, 72%, 62% respectively, p < 0.001). No difference in overall survival was observed between HCV genotypes (p = 0.1). Conclusion: Successful antiviral treatment is associated with superior patient survival in transplanted HCV patients. However, a minority (25%) of patients were considered suitable for treatment. Newly licensed DAAs have superior efficacy and good tolerability in the post-transplant setting. Going forward, the use of DAAs is predicted to have a major impact on graft and patient survival. Disclosure of interest: None Declared.